Eksplorasi Metode Penelitian Ilmu Hukum Kontemporer: Inovasi dan Relevansi dalam Lanskap Hukum Modern - Endarto, Dwi Wahyu; Nasyruddin, Achmad; Nugraha, Bayu Adhy; Jueni, Jueni; Ikbal, Ikbal; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research explores contemporary legal research methods, focusing on their innovations and relevance within the dynamic modern legal landscape. Technological advancements, globalization, and the increasing complexity of legal issues necessitate adaptations in traditional legal research methodologies. This article identifies and analyzes the shift from conventional normative and empirical methods towards more interdisciplinary, multidisciplinary, and technology-driven approaches, such as LegalTech and Artificial Intelligence (AI). The discussion encompasses the role of AI in predictive analytics, natural language processing, and the automation of legal data retrieval, as well as the application of advanced statistics and big data analysis in enhanced quantitative research. Furthermore, in-depth qualitative methods like legal ethnography and complex case studies are also highlighted. This study also examines the implications, ethical challenges, advantages, and limitations of adopting these new methods in legal research practice and education. Thus, this article provides a comprehensive guide for legal researchers to produce relevant, valid, and comprehensive research in the contemporary era.